2018
DOI: 10.3126/jnhrc.v16i2.20308
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Burden in Caregivers of Children with Autism Spectrum Disorder in Kathmandu Valley

Abstract: Background: Autism Spectrum Disorder is a lifelong developmental disorder that affects children and results in deficit in social interaction, communication and display of unusual pattern of behavior. Though caregiving is a normal parental duty, providing intensive care to a child with long-term problem is burdensome and impacts both physical and mental health of caregivers. The aim of this study was to obtain a picture of burden among caregivers raising children with Autism Spectrum Disorder.Methods: We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(29 reference statements)
0
10
0
5
Order By: Relevance
“…One study from India showed that mothers of children with ASD experience stress due to low awareness and reduced accessibility to therapy services (Divan et al, 2012;Patra et., 2015). In this study, most of the children were diagnosed with ASD, providing a common platform for brainstorming solutions in the groups.…”
Section: Discussionmentioning
confidence: 99%
“…One study from India showed that mothers of children with ASD experience stress due to low awareness and reduced accessibility to therapy services (Divan et al, 2012;Patra et., 2015). In this study, most of the children were diagnosed with ASD, providing a common platform for brainstorming solutions in the groups.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, el trabajo de Cid-García (2016) evidencia que el grado de severidad del trastorno del espectro autista se correlaciona significativamente con la presencia de sintomatología depresiva en el cuidador primario. Además, la sobrecarga está relacionada con el estado emocional y la vida social de los cuidadores, la cual se puede encontrar disminuida o reducida (Pandey & Sharma, 2018). Por otra parte, se ha evidenciado que las características personales no son significativas en el índice de sobrecarga (Misquiatti et al, 2015).…”
Section: Discussionunclassified
“…Items ask how the caregivers feel, and responses range from 0 to 4 (never to nearly always). The ZBI has been used to assess burden among caregivers of individuals with ASD [62-68]. Using the ZBI, caregivers of individuals with ASD have been found to experience greater burden of care than other caregivers [63] and burden was related to unmet need in young people with ASD, for example, depression, anxiety, and inappropriate behavior [61,69].…”
Section: Methodsmentioning
confidence: 99%